Pengaruh struktur modal, ukuran perusahaan, dan perencanaan pajak terhadap profitabilitas - Ida Ayu Lestari; Wulandari Agustiningsih (LPMP Imperium, 2023)
Profitability is essential for the company for its survival. This study aimed to determine the effect of capital structure, company size, and tax planning on the profitability of health sector companies listed on the Indonesia Stock Exchange in 2018-2021. The implementation of this research uses a causality associative research design with secondary data types. The sampling technique used purposive sampling and obtained as many as 15 companies that met the criteria from a total population of 23 companies with a research period of 4 years so that 60 sample data were obtained. This study utilizes a multiple linear regression analysis model. The results showed that capital structure (Debt to Equity Ratio) did not affect profitability (Return On Assets), while company size (Size) and tax planning (Tax Retention Rate) had a positive effect on profitability (Return On Assets). Public interest statement Future researchers are expected to consider or add other variables affecting profitability, such as sales growth, leverage, dividend policy, inflation rates, and interest rates on different research objects. Factors from company size and tax planning can be used as the primary reference for companies to increase their profitability.